Supply chain management in the drug industry delivering patient value for pharmaceuticals and biologics - Rees, Hedley (Hoboken, New Jersey Wiley, 2011)
"This book bridges the gap between practitioners of supply-chain management and pharmaceutical industry experts. It aims to help both these groups understand the different worlds they live in and how to jointly contribute to meaningful improvements in supply-chains within the globally important pharmaceutical sector. Scientific and technical staff must work closely with supply-chain practitioners and other relevant parties to help secure responsive, cost effective and risk mitigated supply chains to compete on a world stage. This should not wait until a drug has been registered, but should start as early as possible in the development process and before registration or clinical trials"--Provided by publisher.
PART III: PLANNING AND EXECUTING SUPPLY CHAIN CHANGE. -- CHAPTER 14 IMPROVEMENT IN PHARMACEUTICALS. -- 14.1 Where are we now? -- 14.2 Subsequent developments since inception. -- 14.3 A Blueprint for Quality by Design (QbD). -- CHAPTER 15 EXEMPLAR THINKING IN ORGANISATIONAL IMPROVEMENT. -- 15.1 Where are we now? -- 15.2 What is meant by 'Exemplar'? -- 15.3 A dialogue on exemplar improvement. -- CHAPTER 16 BUILDING A FOUNDATION FOR SUSTAINABLE CHANGE. -- 16.1 Focus on the individual. -- 16.2 Individuals as leaders. -- 16.3 Individuals as motivators and the motivated. -- 16.4 Individuals as group members. -- 16.5 Individuals as participants in cultural change. -- 16.6 CASE STUDY MILES LTD., BRIDGEND, GLAMORGAN. -- CHAPTER 17 A CURE FOR THE PHARMACETICAL SUPPLY CHAIN. -- 17.1 What is the disease state? -- 17.2 What is the label claim for the Medicine? -- 17.3 What will life hold without the medicine? -- 17.4 What is this 'better way' to develop drugs? -- 17.5 Full scale production of drugs. -- 17.6 What are the barriers to change? -- 17.7 What are the potential benefits of change? -- 17.8 Defining the art of the possible. -- 17.9 Concluding message.
Includes bibliographical references and index.
Keywords: Pharmaceutical industry -- Materials management